Yield optimization in isabgol through improved seed and fertilizer management practices in Transitional Plain of Luni Basin of Rajasthan (Indian Journal of Arid Horticulture, 2013)
Field studies were conducted to evaluate the significant varieties/ genotypes and fertilizer management practices  for harvesting the higher seed yield of isabgol in Transitional Plain of Luni Basin of Rajasthan. The maximum seed yield of  14.31 q/ha was provided by variety RI 89 followed by RI 3025 and GI 2 with 14.10 and 13.67 q/ha, respectively. The  application of FYM @ 10 t/ha and biofertilizers (PSB & Azotobactor) along with chemical fertilizers @ 30kg N + 25 kg  P2O5/ha provided 32.92% increase in seed yield of isabgol over farmer’s practice. The use of improved seed with  recommended seed rate of 5 kg/ha along with foliar spray of 1% soluble NPK at flowering stage also provided 27.35%  increase in seed yield over farmer’s practice.
Keywords: Foliar nutrition; improved seed; integrated nutrient management; isabgol; seed yield